2012
DOI: 10.1515/revneuro-2012-0063
|View full text |Cite
|
Sign up to set email alerts
|

The role of the basal ganglia in motivated behavior

Abstract: The present paper reviews foundational and contemporary theories of motivated behaviors and the growing body of evidence that they require specific functional interactions within the basal ganglia. Such evidence suggests that unconditioned responses (UR), conditioned responses (CR), goal-directed actions and stimulus-response (S-R) habits are selected in the basal ganglia. Such selection depends on activation of striatal neurons by cortical and subcortical neurons encoding unconditioned stimuli (US), condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…A growing body of evidence has shown that the BG forms a neural network dedicated to selection (Nicola, 2007; Redgrave et al, 2008, 2010; Da Cunha et al, 2009, 2012; Grillner et al, 2013). The strongest evidence is related to action-selection by the cortico-BG motor loop (Frank and Claus, 2006; Frank, 2011; Isoda and Hikosaka, 2011; Mink, 1996; Mogenson et al, 1980).…”
Section: Bg Cortico-thalamic Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has shown that the BG forms a neural network dedicated to selection (Nicola, 2007; Redgrave et al, 2008, 2010; Da Cunha et al, 2009, 2012; Grillner et al, 2013). The strongest evidence is related to action-selection by the cortico-BG motor loop (Frank and Claus, 2006; Frank, 2011; Isoda and Hikosaka, 2011; Mink, 1996; Mogenson et al, 1980).…”
Section: Bg Cortico-thalamic Loopmentioning
confidence: 99%
“…The BG has been proposed as a system to make selections: action-selection, reasoning/cognition related selections, and motivational state selections (Da Cunha et al, 2009, 2012; Redgrave et al, 2011). Understanding how the cortico-BG circuitry is suited for such computations is critical to understand how electrical stimulation of parts of this system can improve and/or motor and psychicatric functions.…”
Section: Introductionmentioning
confidence: 99%
“…It includes DA neurons of the ventral tegmental area (VTA), projecting to prefrontal cortex (PFC) and limbic areas (e.g., ventral striatum), and DA neurons of the substantia nigra (SN), projecting to the dorsal striatum (6). Involvement of the midbrain DA system is strongly implicated in both the cognitive and motivational deficits observed in schizophrenia (7,8). Moreover, it is well documented that the DA system is altered in patients with schizophrenia (reviewed in refs.…”
mentioning
confidence: 99%
“…The striatum occupies a central role in signal attenuation throughout the basal ganglia circuitry that is involved in cognition, emotional processes, and motor responses. Several recent review articles detail the intricacies of this brain region [36][37][38][39][40]. It has been hypothesized that two main circuits signal from the striatum: (1) the striatopallidal/indirect pathway and (2) the striatonigral/direct pathway.…”
Section: Circuitrymentioning
confidence: 99%